Experimental and simulation investigation on heat transfer characteristics of supercritical nitrogen in a new rib tube of open rack vaporizer. (March 2020) - Cheng, He; Ju, Yonglin; Fu, Yunzhun
Highlights: A new rib tube with petal-shaped internal fins is designed and tested for ORV. Heat transfer characteristics in smooth and rib tube are experimentally studied. The effects of different operating parameters on heat transfer are investigated. Numerical simulation is conducted to further analyze the heat transfer behaviors. A new correlation is developed to accurately predict the heat transfer coefficient. Abstract: Open rack vaporizer (ORV), using seawater as heat source, is widely used in liquefied natural gas (LNG) receiving terminals. In this study, a new rib tube, with petal-shaped internal fins and rectangular straight external fins, is designed and tested. A series experiments are conducted to investigate the heat transfer and pressure drop characteristics of the supercritical nitrogen flow in the new rib tube and the smooth tube. The heat transfer coefficient of the rib tube is 66.3% larger than that of the smooth tube, and the frictional pressure drop in the rib tube is also smaller compared to that of the smooth tube. Different control variables affecting the heat transfer characteristics in the rib tube are studied, including the temperature of the water, the mass flow rate and the pressure of the nitrogen. Meanwhile, numerical simulation is conducted to further analyze the heat transfer coefficients near the pseudo-critical region. A new correlation is developed to accurately predict the heat transfer coefficients of the supercritical fluid in the new rib tube based on the experimental and simulation data. The new correlation shows a good agreement as 95% of the experimental data captured with an error within 20%. This study may provide reference for the research on the supercritical fluid flow and the heat transfer enhancement of the tube in ORV.